THE EFFECT OF SPECIFIC EXERCISES ON DEVELOPING KEY MOTOR ABILITIES AND BASKETBALL SHOOTING SKILL PERFORMANCE IN FEMALE STUDENTS - hussein hassan, Wasan Abdul (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
This research examines the impact of specific exercises on improving motor abilities and basketball shooting skills in female students. The study highlights basketball as a sport requiring high motor skills and physical abilities, particularly shooting, which is essential for winning. The research problem was identified as a lack of effective training methods and inadequate training curricula, resulting in weak development of fundamental motor skills, such as speed and precision, negatively impacting female students' performance. The experimental method was applied to a sample of 30 female students divided into a control and an experimental group. A tailored training program consisting of 24 sessions over three months was implemented, utilizing educational tools such as videos and CDs to enhance performance. Results showed significant improvements in motor abilities (e.g., speed and explosive strength) and basketball shooting skills in the experimental group compared to the control group. The study concludes that specific exercises effectively enhance students' motor and skill capabilities. It recommends incorporating such exercises into training curricula and suggests future studies to assess their impact on other sports.